Aggregation‐induced emission systems involving supramolecular assembly. Issue 1 (29th December 2020) - Lou, Xin‐Yue; Yang, Ying‐Wei
Abstract: Aggregation‐induced emission (AIE), as an exciting photophysical phenomenon, has been regarded as one frontier research topic within both ranges of molecular luminescence and materials science over the last two decades. Since controllable molecular ensembles with particular morphologies and tunable functions can be elegantly constructed in the realm of supramolecular chemistry, the integration of supramolecular assembly and AIE systems can expectedly bring about luminescent materials with tunable emission and tailorable well‐ordered architectures. In this review, we will provide a summary of the creation and working mechanisms of AIE systems involving supramolecular systems that are driven by different supramolecular driving forces including hydrogen bonding, host−guest interactions, metal coordination, and π–π interactions. The morphological and photoluminescent features of these AIE‐active supramolecular assemblies will be elucidated, and the regulated fluorescence properties of the AIEgens induced by the assembling–disassembling processes will be discussed in detail. Abstract : AIE systems involving supramolecular assembly are illustrated, where the assembly processes are driven by hydrogen bonding, host−guest interactions, metal coordination, and π–π interactions. The most recent advances in this very field are discussed in detail, covering the construction methods of the assemblies with different morphologies, the adjustable fluorescence properties of the assembled AIEgens, and the structure–property linkage of these systems.